PENGGUNAAN MEDIA PEMBELAJARAN KIMIA BERBASIS LECTORA INSPIRE UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN PENCEMARAN LINGKUNGAN KELAS VII IPA SMPN 32 PEKANBARU - Syaputra, Yandri; Herdini, Herdini; Abdullah, Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aimed of the research was to improve students' learning achievement on the topic of environmental pollution in class VII of SMPN 32 pekanbaru. The form of the research was an experiment with a randomized control group pretest-posttest research design. The sample in this research was class VII2 as an experimental class and class VII3 as a control class that was randomly determined after normality testing was done using the liliefors test and homogeneity test, using the two variance similarity test and the average similarity test. The experimental class was treated with the use of lectora inspire-based learning media, while the control class without the use of lectora inspire-based learning media. Data analysis for hypothesis testing is performed using the right-hand t-test. Based on the results of the analysis of data processing, it is obtained tcount> ttable which is 3.11> 2.00 which means the use of lectora inspire-based chemistry learning media can improve students' learning achievement on the subject of environmental pollution in class VII IPA of SMPN 32 Pekanbaru. Key Words: Lectora Inspire, Learning Media, Learning Achievement, Environmental Pollution